Sarcasm in Social Media: A Study of Comments on Sam Smith's Instagram Posts - Iraisha Fadilah; Agus Wijayanto (Universitas Cokroaminoto Palopo, 2024)
This study aims to explain the types of sarcasm expressions and determine the purpose of sarcsm used by netizens in Sam Smith's Instagram comment column. Descriptive qualitative was used in this research. The objects of the research were sarcasm in netizen comments on Sam Smith's Instagram posts and their intended meaning. Documentation was employed to collect the research data and content analysis was employed to observe the sarcasm. The findings revealed that four types of sarcasm were used by netizens to comment Sam Smith's Instagram posts, including propositional, lexical, like - prefix, and illocutionary sarcasm. The study found five purposes of sarcasm: sophistication, evaluation, politeness, persuassive communication, and retraction.